FAKTOR YANG MEMPENGARUHI PASIEN POST OP FRAKTUR UNTUK MELAKUKAN RANGE OF MOTION (ROM) - Igiany, Prita Devy (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2018)
Range Of Motion (ROM) is an exercise performed to maintain or improve the ability to move the joints normally to increase muscle mass and tone. ROM is performed in patients with post-op fractures with the aim of reducing the risk of contractures and preventing thrombus formation in post-op fracture patients. This study aims to determine the factors that influence post-op fracture patients to perform ROM in Cendrawasih Room II Arifin Achmad Hospital Pekanbaru. This study is a correlational study that is research that examines the relationship between variables, where the results of the study were analyzed using Fisher and Chi Square. Sampling in this study was purposive sampling with the number of respondents as many as 30 respondents from the population of post-op fracture patients. The results of this study indicate that there is no significant relationship between pain and knowledge of ROM implementation with a value of p> 0.05. Based on the results of statistical tests for family support, there is a relationship between family support for the implementation of ROM with p <0.05.Keywords: post-op fracture, range of motion